2018
DOI: 10.15835/nbha46110939
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Biological Control of Fusarium oxysporum Using Trichoderma spp., on Soil and Rockwool Substrates in Controlled Environment

Abstract: Medicinal plant cultivation in Controlled Environment (CE) is increasing in the context of the new findings concerning the abiotic stress factors manipulation that leads to a significant increment in bioactive substances. Pathogen control is a vital part of the cultivation system, therefore the study was focused on biological methods of controlling a frequently occurring disease, by inoculating the sterile substrates specific in hydroponics, with the beneficial organism. Hypericum perforatum seedlings were ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…In recent years, Trichoderma spp. has been used as biocontrol agents to control different plant pathogens [20,21]. Specifically, previous studies have reported that T. viride MTCC No.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Trichoderma spp. has been used as biocontrol agents to control different plant pathogens [20,21]. Specifically, previous studies have reported that T. viride MTCC No.…”
Section: Discussionmentioning
confidence: 99%
“…The alterations caused by vascular wilt on the leaf gas exchange properties and wf had a negative effect on total biomass accumulation (TDW) in most of the evaluated genotypes, except for P. floridana plants. Giurgiu et al (2018) and Chávez-Arias et al (2019) also recorded a reduction in biomass accumulation with periods of FO inoculation greater than 15 days in St. John's wort and cape gooseberry plants, respectively, with a reduction of water and nutrient uptake and an indirect decrease of the synthesis of photosynthetic pigments (Pantelides et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Trichoderma spp. foi inoculado em plantas de Hypericum perforatum (erva-de-sãojoão), e ocorreu o melhor desenvolvimento das raízes, contudo na temperatura entre 21 °C e 23 °C (GIURGIU et al, 2018).…”
Section: Discussionunclassified